Cysteine and obesity: consistency of the evidence across epidemiologic, animal and cellular studies. - Elshorbagy, A; Kozich, V; Smith, A; Refsum, H (2012)
PURPOSE OF REVIEW: The concentrations of several plasma amino acids increase in obesity. Notably, plasma total concentrations of the sulphur amino acid cysteine (tCys) are linearly associated with fat mass in large population studies. Animal and cellular experiments support the concept that cysteine may be obesogenic. Here we review experimental and epidemiologic findings linking cysteine and related compounds with fat regulation and obesity. RECENT FINDINGS: tCys, and to a lesser extent cystathionine, are the only plasma sulphur amino acids consistently associated with human obesity, whereas glutathione is inversely associated with BMI. Supplementing cyste(i)ne in rodents decreases energy expenditure and promotes adiposity, whereas defects of cysteine-synthesizing enzymes decrease body weight. In adipocytes, cysteine inhibits lipolysis and promotes lipogenesis via H2O2 production. Unlike most plasma amino acids, tCys levels do not decrease with gastric bypass-induced weight loss, further supporting the concept that elevated cysteine may be a cause, not a consequence of obesity. Although cysteine products (glutathione, taurine and H2S) are altered in obesity, they do not appear to explain cysteine's effects on body weight. SUMMARY: Cellular, animal and epidemiologic data are consistent with the view that cysteine is obesogenic. Targeted research linking in-vitro and in-vivo findings is needed to elucidate mechanisms involved.